PERANAN ONLINE TRAVEL AGENT DALAM MENINGKATKAN BOOKINGAN KAMAR UNTUK MEMBANTU TERCAPAINYA TARGET REVENUE DI CAVINTON HOTEL YOGYKARTA - Rahayu, Enik; Hendrajaya (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The hospitality industry in Yogyakarta faces intense competition, prompting hotels like Cavinton Hotel Yogyakarta to adopt innovative strategies, including leveraging Online Travel Agents (OTA) as their primary distribution channel. This research aims to identify Marketing Strategies through OTAs at Cavinton Hotel Yogyakarta, analyze the Impact of OTA Usage on Target Revenue Achievement, and explore Guest Experiences in Booking Through OTAs. The research methodology employed is a qualitative approach with a case study, involving interviews with the Marketing Manager of Cavinton Hotel, OTA Account Manager, and Hotel Guests who booked through OTAs. The findings indicate that marketing strategies through OTAs have significantly increased the hotel's visibility, room bookings, and revenue. This positive impact is evidenced by a revenue increase of up to 30% from OTA bookings. Guest experiences in booking through OTAs are also generally satisfactory, with most guests feeling that the process provides ease and convenience in booking. This research provides comprehensive insights into the role of OTAs in boosting room bookings and achieving target revenue at Cavinton Hotel Yogyakarta, along with practical recommendations for hotel management and the hospitality industry at large